2018
DOI: 10.1007/s10266-018-0373-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of irrigation strategies on the removal of the smear layer from root canal dentin

Abstract: The aim of this study was to evaluate the removal of the smear layer by some commonly used (needle-and-syringe irrigation, sonic activation, ultrasonically activated irrigation) and new root canal irrigation strategies (negative pressure irrigation and polymer rotary file) using a novel approach by comparing pre- and post-experimental images. Prepared root canals (n = 50) were subjected to a split tooth model and divided into 5 groups (n = 10): (1) needle-and-syringe irrigation (control); (2) sonic activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
13
1
3
Order By: Relevance
“…This result could be due to the fact that sonic frequency ranges are much lower than ultrasonic irrigation, and therefore the acoustic microstreaming would be lower, as would be the cleaning efficacy. [ 33 ] This study’s results were inconsistent with the above findings, may be because a different irrigation duration, and regime was applied.…”
Section: Discussioncontrasting
confidence: 73%
“…This result could be due to the fact that sonic frequency ranges are much lower than ultrasonic irrigation, and therefore the acoustic microstreaming would be lower, as would be the cleaning efficacy. [ 33 ] This study’s results were inconsistent with the above findings, may be because a different irrigation duration, and regime was applied.…”
Section: Discussioncontrasting
confidence: 73%
“…1,26 The aim to achieve 3-dimensional cleaning of the root canal space is not possible without irrigation solution reaching the apical one third of the working length followed by activation of irrigant with different activation methods as areas like isthmuses, apical deltas etc are not negotiable even with modern canal preparation methods. 25 In this survey 45.2% of the dentists were not using any irrigant activation method to increase the efficacy of irrigant whereas only 24.4 % used manual method of irrigant activation. With growing evidence, it has become evident that irrigant activation with ultrasonics, sonic activation, or negative pressure devices is very important for irrigant penetration in to the apical one third of the canal for achieving maximum disinfection of the canal.…”
Section: Discussionmentioning
confidence: 77%
“…24 Intracanal irrigation with 0.5-5.25% sodium hypochlorite is considered a gold standard antimicrobial agent to dissolve organic component of smear layer. 25 In this study the use of sodium hypochlorite primarily after access opening was practiced by 68.5% of the dentists. The results are consistent with the findings of studies done by Palmer et al in UK who reported 75% and Unal et al in Turkey showed 73% of the dentists practiced use of sodium hypochlorite primarily after access opening.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The different methods of the root canal preparation result in formation of this coating; comprised of 2 areas: outer most organic layer which is about two microns, then subsequent area stretches out to dentinal tubules to a profundity of 40microns and is to a great extent made of dentin chips. (14). Moreover, achieving clean patent dentinal walls through eradication of this layer is necessary to enhance the smooth hermetic sealing of the entire configuration.…”
Section: Discussionmentioning
confidence: 99%